2009
DOI: 10.1126/science.1165712
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Temperature Preferences and Energy Homeostasis in Dystroglycan Mutants

Abstract: Temperature affects the physiology, behavior, and evolution of organisms. We conducted mutagenesis and screens for mutants with altered temperature preference in Drosophila melanogaster and identified a cryophilic (cold-seeking) mutant, named atsugari (atu). Reduced expression of the Drosophila ortholog of dystroglycan (DmDG) induced tolerance to cold as well as preference for the low temperature. A sustained increase in mitochondrial oxidative metabolism caused by the reduced expression of DmDG accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 19 publications
2
61
0
2
Order By: Relevance
“…We found that this experiment is easy, quick to conduct and generates reproducible data that is in agreement with other studies 1,6,9 . The protocol outlined here can be easily modified to fit any laboratory's budget and available materials.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We found that this experiment is easy, quick to conduct and generates reproducible data that is in agreement with other studies 1,6,9 . The protocol outlined here can be easily modified to fit any laboratory's budget and available materials.…”
Section: Discussionsupporting
confidence: 78%
“…Despite the more complex equipment, the sensitivity of the method described here is similar to reported values ( Table 1). Additionally, several other groups have used variations of this technique to determine relative metabolic rates in Drosophila [4][5][6] . Therefore, this assay can be used to generate reliable, reproducible data relevant to Drosophila metabolism without the purchase of specialized equipment which can be setup in any lab and can be used for educational purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, there have been cases reporting that the alteration of transcription level of some genes can induce similar physiological responses to those observed in our study. For example, both metabolic rate and cold tolerance were enhanced in atsugari and fumin mutants due to the altered transcription level of the corresponding and/or downstream genes (Takeuchi et al, 2009;Ueno et al, 2012). Secondly, Smp30 (Dca), known as a candidate gene for cold tolerance, was up-regulated during the cold acclimation at 15°C for a few days in D. melanogaster originally reared at 25°C, a condition similar to that of our study (Goto, 2000).…”
Section: Discussionmentioning
confidence: 50%
“…The connection between cold tolerance and metabolic rate was also suggested in studies of D. melanogaster mutants. A mutant of dystroglycan gene, atsugari, which causes an increase in mitochondrial oxidative metabolic rate, showed a higher cold tolerance (Takeuchi et al, 2009). Similarly, a dopamine transporter-defective mutant, fumin, showed a higher metabolic rate and a higher cold tolerance (Ueno et al, 2012).…”
Section: Introductionmentioning
confidence: 99%